Analisis Peran Hubungan Masyarakat pada PT. Prima Mitra Elektrindo - Bunga Fadilla; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Universitas Maritim AMNI Semarang, 2023)
Public relations is a communication activity between a company, agency or organization and the public. Therefore, public relations plays an important role for an organization to establish good relations with the public. This research uses a qualitative descriptive approach, namely by analyzing behavior or actions that occur narratively. The data sources in this research use primary and secondary sources. Primary data is data obtained from observation, interviews and documentation. Meanwhile, secondary data is data obtained from research journals, books and research articles. The sampling technique in this research used a purposive sampling technique. The purposive sampling technique is a sampling technique that takes information from an informant who has the potential to know the data needed in the research. The aim of this research is to understand the role of public relations in depth at PT. Prima Mitra Elektrindo. The results of this research indicate that the role of public relations at PT. Prima Mitra Elektrindo has done this optimally.